Philippines Economic Update, October 2017 : Preserving Consistency and Policy Commitment - World Bank (Washington, DC, 2017)
The Philippines Economic Update (PEU) summarizes key economic and social developments, important policy changes, and the evolution of external conditions over the past six months. It also presents findings from recent World Bank analysis, situating them in the context of the country’s long-term development trends and assessing their implications for the country’s medium-term economic outlook. The PEU covers issues ranging from macroeconomic management, financial-market dynamics to the complex challenges of poverty reduction and social development. It is intended to serve the needs of a wide audience, including policymakers, business leaders, private firms and investors, and analysts and professionals engaged in the social and economic development of the Philippines. Policymakers need to confront downside risks while fostering long-term growth. The short-term risks to the country’s outlook include increased trade protectionism, the possibility of financial market disruptions, and elevated economic policy uncertainty. In the longer term, weaker growth potential remains the main risk. Consistency in the government’s policies to achieve stable inflation, fiscal stability, and security will help preserve consumer and business confidence. For the Filipino consumer, it will be important that inflation remains at moderate levels. This will warrant careful inflation management by the central bank authorities to anchor expectations. As long as it is consistent with medium-term fiscal sustainability, an expansionary fiscal policy could support short-term growth. The successful and timely implementation of the government’s fiscal program, including its ambitious infrastructure plan and efforts to generate more revenue, would signal a strong commitment to the government’s policy priorities. Key issues, such as mining regulations and regional development in Mindanao, will require policy certainty to preserve both external and domestic confidence in the Philippine economy. Implementing structural policies that support investment and trade will be critical to boost productivity and potential growth in the long-term. These policies would require the government’s commitment to reforms that promote competition in key sectors, secure property rights, lessen regulatory complexities, and improve doing business in the country. Longer-term policy priorities also include training and job search programs and other measures to support workers most affected by sectoral shifts in employment and share the dividends of growth and gains from globalization more widely. Sustained investment in human capital development and in sectors that create quality employment are needed to safeguard the country’s progress on delivering inclusiveness.